The Effectiveness of Class Management-Based Role-Playing Method on The Learning Outcomes of Fifth-Grade Elementary School Students In Pancasila Education - Tika Rahmawati; Herry Sanoto (Eduvest - Journal of Universal Studies, 2025)
This research investigates the effectiveness of a class management-based role-playing learning method on the learning outcomes of fifth-grade elementary school students in Pendidikan Pancasila. This research is a quasi-experiment with a pretest-posttest control group design. The research population consisted of 48 students divided into two groups: an experimental group and a control group. Data were collected based on the posttest results, which consisted of multiple-choice questions that had been previously tested for validity and reliability. Data analysis included normality testing, homogeneity testing, independent samples T-test, and N-gain analysis. The results of the research showed a difference in the mean posttest scores (experimental group = 65.54; control group = 51.00). The independent samples T-test showed a Sig. (2-tailed) value of 0.000 (<0.05) with an N-gain value of 46.4135, indicating a significant difference in learning outcomes between the two groups. In conclusion, the application of a class management-based role-playing method can effectively improve learning outcomes in Pendidikan Pancasila, particularly in the material "Kronologi Sejarah Kelahiran Pancasila".